PERAN KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL DALAM MEMODERASI MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN - 11.42.02.0046, Judhi Tjahjanto (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research aims to examine the effect of earnings management, managerial ownership and institutional ownership on firm value and managerial ownership, and examines the role of institutional ownership in moderate earnings management on firm value.Sample in this study is a manufacturing sector that has been listed on the Jakarta Stock Exchange, which publishes annual financial statements during the observation period 2009, 2010 and 2011, which have data institutional ownership and managerial ownership and always make a profit. Data analysis using classical assumption, normality test, mulcollinearity, autocorrelation test and test heterokedastisitas, hypothesis testing using multiple regression.The result of this study indicate that earnings management, managerial ownership and institutional ownership has no effect on firm value. Managerial ownership doen not moderate the relationship between earning management and corporate value, while institutional ownership moderates the relationship between earnings management and firm value. Key words: Earnings management,Managerial Ownership, Institutional Ownership, Firm value